Macrozoobenthos as Bioindicators of Water Quality in a Managed and Restored Tropical River: A Case Study of the Upper Citarum River - Timuria Cahyani, Nadya; Chazanah, Nurul; Suharyanto; Wulandari, Suci; Baranovtaria, Brima; Rayhan Firdaus Fahmi, Muhammad; Haekal Fikri, Muhammad (Jurnal Teknik Lingkungan, 2026)
Macrozoobenthos and physicochemical water parameters were sampled at five stations along an upstream–downstream gradient from July to September 2025. Community structure was assessed based on taxonomic composition, abundance, and diversity indices, while spatial patterns were explored using non-metric multidimensional scaling (nMDS), hierarchical cluster analysis, and SIMPER. Associations between macrozoobenthos metrics and environmental variables were examined using Spearman’s rank correlation. The results revealed pronounced spatial variation in water quality and macrozoobenthos communities along the river. Upstream sections were characterized by higher dissolved oxygen, coarser substrates, and the presence of environmentally sensitive insect taxa, indicating relatively good ecological condition. Midstream sections exhibited transitional conditions with mixed assemblages of sensitive, semi-tolerant, and facultative taxa. In contrast, downstream sections were dominated by highly tolerant taxa with low diversity and high dominance, reflecting degraded ecological conditions associated with organic loading, suspended solids, nutrient enrichment, and reduced dissolved oxygen. These findings support the application of macrozoobenthos as reliable bioindicators for water quality assessment in tropical river systems.